A new mite of the genus Alliphis Halbert, 1923 from Iran (Acari: Eviphididae), with a summary of the world fauna - Mašán, Peter; Babaeian, Esmaeil; Kafi, Pouneh (Zootaxa, 2016)
A new species of mite belonging to the genus Alliphis Halbert, 1923 is described from Iran. The description of Alliphis carinatus Mašán & Babaeian, sp. nov., is based on females collected on an unidentified coprid beetle of the genus Copris Geoffroy, 1762. The new species is unusual in having a strongly sclerotised dorsal shield with longitudinally oriented ridges. Among the 37 species which are or have been included in the genus Alliphis, only 15 of them can be now reliably classified within the genus, excluding Alliphis siculus (Oudemans, 1905) and Alliphis transversus Halliday, 2010, which probably require the new genera. Alliphis halberti Ryke & Meyer, 1957, Alliphis serrochaetae Ramaraju & Mohanasundaram, 1996 and Alliphis trichiensis Ramaraju & Mohanasundaram, 1996, are newly transferred to Alloseius Mašán & Halliday, 2009 (Eviphididae), Neopodocinum Oudemans, 1902 (Macrochelidae) and Copriphis Berlese, 1910 (Eviphididae), respectively.